Nihilent Technologies : recommending change at The Banking Association of South Africa - Metton, Eulalie; Rijamampianina, Rasoava ([London] : SAGE, 2016)
In July 2008, Indian management consulting company, Nihilent Technologies, started work on the tender it had won to install a performance management system at The Banking Association South Africa - a project it called Project Masibambane - 'Let's Hold Hands'. The project name came out of a competition that the team held during the kick-start of the project.
Originally Published in: Metton, E. & Rijamampianina, R. (2010). Nihilent: Recommending Change at The Banking Association South Africa (B). WBS-2010-5. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Banking Association South Africa; Employees -- Rating of -- Case studies; Corporate turnarounds -- Case studies; Organizational change -- Case studies